THE EFFECT OF THE GAME LANGKAH TAPAK GMBIRA ON THE GROSS MOTOR DEVELOPMENT OF EARLY CHILDREN - Sudarmi, Sudarmi; Khasanah, Imroatul; Septiani, Ranny (Indonesian Journal of Health Science, 2025)
The ages of 5–6 years represent a golden period in child development, during which gross motor skills undergo rapid growth. Nevertheless, some children continue to experience developmental delays due to limited stimulation. This study investigated the effect of the Lantara game, a structured physical activity, on the gross motor skills of children aged 60–72 months at TK Gelora Mekar, Way Tenong District, West Lampung Regency, in 2025. A quantitative approach with a one-group pretest–posttest design was employed. The sample consisted of 22 children selected according to inclusion and exclusion criteria. Data were obtained through observation and standardized gross motor assessments administered before and after the intervention. Statistical analyses included normality testing and paired sample t-tests. The results demonstrated significant improvements in all domains of gross motor skills following the intervention: Jump on one leg increased from 2.23 to 3.91,  Stand on one leg for several seconds, from 2.32 to 3.82, Walk in a straight line,  from 2.36 to 3.95, and Jump forward from 2.36 to 3.95 (p < 0.05). These findings indicate that the Lantara game is an effective medium for stimulating gross motor development in early childhood. Its application may serve as a practical, play-based strategy to address developmental delays and promote holistic growth in preschool settings.